Physician Introduction to Opioids for Pain Among Patients with Opioid Dependence and Depressive Symptoms - Tsui, Judith I. (2010)
This study determined the frequency of reporting being introduced to opioids by a physician among opioid dependent patients. Cross-sectional analyses were performed using baseline data from a cohort of opioid addicts seeking treatment with buprenorphine. The primary outcome was response to the question: “Who introduced you to opiates?” Covariates included sociodemographics, depression, pain, current and prior substance use. Of 140 participants, 29% reported that they had been introduced to opioids by a physician. Of those who were introduced to opioids by a physician, all indicated that they had initially used opioids for pain, versus only 11% of those who did not report being introduced to opioids by a physician (p<0.01). There was no difference in current pain (78% vs. 85%, p=0.29), however participants who were introduced to opioids by a physician were more likely to have chronic pain (63% vs. 43%, p=0.04). A substantial proportion of individuals with opioid dependence seeking treatment may have been introduced to opioids by a physician.